Constitutional Internet Blocking: Sebuah Upaya Preemtif terhadap Digital Authoritarian dalam Perspektif Negara Hukum Demokratis - Nugraha, Xavier; Regita Nathalia, Angeline; Emely Laurentius, Melva (Universitas Negeri Surabaya, 2023)
The government have issued numerous internet blocking when there are no explicit rules regarding them, such as sources of authority, criteria, deadline, Legal attempt, and so forth. Based on that, the formulation of the problems in this article are first, how is the internet blocking in a perspective of the state of democratic law? Second, how is the constitutional internet blocking mechanism? As for the purposes in this article are first, analyzing internet blocking in the perspective of the state of democratic law and second, describing the constitutional internet blocking mechanism. The research method used in this article is a doctrinal research method with a statute approach, conceptual approach, and case approach. The analysis results for this article are first, internet blocking in the state of democratic law are permissible but must not against the constitution, that is, should not against with the 1945 Constitution and the constitutional court ruling, and in accordance with the principle of human rights protection regulated in International Covenant on Civil and Political Rights (ICCPR). Second, as for the constitutional internet blocking mechanisms are formally expressed in the legal products of laws and materially will be regulated in conjunction with internet blocking procedures, legal subjects who can legally enforce internet blocking, Governments that can specifically implement internet blocking, criteria for internet blocking, deadline of internet blocking, and legal attempt against internet blocking. Keywords: Constitutional Internet Blocking, Digital Authoritarian, Human Rights, State of Democratic Law.